"Proprietary Processed" Allografts: Clinical Outcomes and Biomechanical Properties in Anterior Cruciate Ligament Reconstruction. (November 2017) - Roberson, Troy A.; Abildgaard, Jeffrey T.; Wyland, Douglas J.; Siffri, Paul C.; Geary, Stephen P.; Hawkins, Richard J.; Tokish, John M.
Background: The processing of allograft tissues in anterior cruciate ligament (ACL) reconstruction continues to be controversial. While high-dose irradiation of grafts has received scrutiny for high failure rates, lower dose irradiation and "proprietary-based" nonirradiated sterilization techniques have become increasingly popular, with little in the literature to evaluate their outcomes. Recent studies have suggested that the specifics of allograft processing techniques may be a risk factor for higher failure rates. Purpose: To assess these proprietary processes and their clinical outcomes and biomechanical properties. Study Design: Systematic review. Methods: A systematic review was performed using searches of PubMed, EMBASE, Google Scholar, and Cochrane databases. English-language studies were identified with the following search terms: "allograft ACL reconstruction" (title/abstract), "novel allograft processing" (title/abstract), "allograft anterior cruciate ligament" (title/abstract), "anterior cruciate ligament allograft processing" (title/abstract), or "biomechanical properties anterior cruciate ligament allograft" (title/abstract). Duplicate studies, studies not providing the allograft processing technique, and those not containing the outcomes of interest were excluded. Outcomes of interest included outcome scores, complication and failure rates, and biomechanical properties of the processed allografts. Results: Twenty-four studies (13 clinical, 11 biomechanical) met inclusion criteria for review. No demonstrable difference in patient-reported outcomes was appreciated between the processing techniques, with the exception of the Tutoplast process. The clinical failure rate of the Tutoplast process was unacceptably high (45% at 6 years), but no other difference was found between other processing techniques (BioCleanse: 5.4%; AlloTrue: 5.7%; MTF: 6.7%). Several studies did show an increased failure rate, but these studies either combined processing techniques or failed to delineate enough detail to allow a specific comparison for this study. The biomechanical studies showed overall maintenance of satisfactory biomechanical properties throughout multiple testing modes with normalization to the percentage of control specimens. Conclusion: A comparison of proprietary allograft processing techniques is difficult because of the variability and lack of specificity of reporting in the current literature. Among the available literature, except for the Tutoplast process, no notable differences were found in the clinical outcomes or biomechanical properties. Future study with a longer follow-up is necessary to determine the role and limitations of these grafts in the clinical setting.